2006
DOI: 10.1111/j.1533-2500.2006.00085.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Spinal Cord Stimulation in Refractory Abdominal Visceral Pain: Case Reports and Literature Review

Abstract: Patients will commonly seek medical attention for refractory abdominal pain. The many causes of abdominal pain include pathologies of the gastrointestinal, genitourinary, musculoskeletal, and nervous systems. Unfortunately, a large number of patients will develop chronic abdominal pain that is recalcitrant to definitive therapies and nonspecific treatments such as cognitive-behavioral, physical, and pharmacologic therapies. Although spinal cord stimulation is classically used for neuropathic and ischemic condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 18 publications
3
61
0
Order By: Relevance
“…Tiede et al 90 described treatment of refractory abdominal pain in two patients. Both patients had a significant history including multiple abdominal surgeries and failed conservative measures.…”
Section: Abdominal and Visceral Pain Syndromesmentioning
confidence: 99%
“…Tiede et al 90 described treatment of refractory abdominal pain in two patients. Both patients had a significant history including multiple abdominal surgeries and failed conservative measures.…”
Section: Abdominal and Visceral Pain Syndromesmentioning
confidence: 99%
“…17 Recent clinical case observations have reported efficacy of SCS in other visceral diseases, such as persistent esophageal pain 22 and refractory abdominal pain due to various pathological conditions. 23,24,26,49 With respect to spinal mechanisms, Chandler et al 6 reported that SCS suppresses excitatory responses of thoracic STT neurons to electrical stimulation of cardiopulmonary sympathetic afferents and to intracardiac injection of bradykinin in primates. SCS at upper cervical and lumber segments also suppress responses of lumbosacral spinal neurons to noxious colonic distension and attenuate a nociceptive visceromotor reflex produced by colorectal distension in rats with or without colonic hypersensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated significant involvement of dorsal column pathways in transmission of visceral pain syndrome [3][4][5] . Application of spinal cord stimulation (SCS) for the neuropathic pain, such as failed back surgery syndrome, angina pectoris, peripheral nerve injury pain, causalgia, reflex sympathetic dystrophy have been shown good outcome [3][4][5]7,8,16) . In addition, spinal cord stimulation suppresses visceral response to colon distension in an animal model 3,12,13,16) .…”
Section: Introductionmentioning
confidence: 99%
“…Application of spinal cord stimulation (SCS) for the neuropathic pain, such as failed back surgery syndrome, angina pectoris, peripheral nerve injury pain, causalgia, reflex sympathetic dystrophy have been shown good outcome [3][4][5]7,8,16) . In addition, spinal cord stimulation suppresses visceral response to colon distension in an animal model 3,12,13,16) . Case series in the literature report an effective outcome of SCS on intractable visceral pain [3][4][5]16) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation